IMPLEMENTATION OF VILLAGE GOVERNMENT STRATEGIC PROGRAM IN BODDIE VILLAGE, MANDALLE DISTRICT, PANGKEP DISTRICT - Rahmi Rais; Dian Pratiwi; A.Ariyadi (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal